2020
DOI: 10.1080/21663831.2020.1713244
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-free geometric recrystallisation in a metastable β-Ti alloy produced by selective laser melting

Abstract: Super-transus heat treatments conducted on an additively manufactured body-centred-cubic β-Ti alloy led to the formation of equiaxed β grains from an initially columnar structure. The grain structure was transformed thanks to a combination of Plateau-Rayleigh instability and grain growth driven by reduction in grain boundary surface area. This is a new type of geometric recrystallisation with no deformation involved. Other mechanisms proposed based on either deformation-induced recrystallisation or martensitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Previous references have demonstrated that a heat treatment temperature lower than Tβ prompted the precipitation of α phase, which would impede the growth of β grain boundaries [19,20]. As for the processing temperature higher than Tβ, the columnar grains were driven to become equiaxed due to the combination of Plateau-Rayleigh instability and the surface tension reduction in grain boundary surface area [30]. After αβ-STA, the metastable β structure converted to a bimodal structure with equiaxed αp and acicular αs phases (see Figure 8c).…”
Section: The Microstructure and Phase Of Heat-treated Samplementioning
confidence: 99%
“…Previous references have demonstrated that a heat treatment temperature lower than Tβ prompted the precipitation of α phase, which would impede the growth of β grain boundaries [19,20]. As for the processing temperature higher than Tβ, the columnar grains were driven to become equiaxed due to the combination of Plateau-Rayleigh instability and the surface tension reduction in grain boundary surface area [30]. After αβ-STA, the metastable β structure converted to a bimodal structure with equiaxed αp and acicular αs phases (see Figure 8c).…”
Section: The Microstructure and Phase Of Heat-treated Samplementioning
confidence: 99%
“…[3] In addition, EBM process is carried out in a vacuum chamber with a high temperature (600-700 C), which is favorable to residual stress minimization and equilibrium phase formation. Some traditional Ti alloys, including Ti-6Al-4V, [9][10][11] Ti-5Al-2.5Sn, [12] Ti-5Al-5Mo-5V-3Cr [13,14] and its close variants [15][16][17] etc., have been explore their suitability in SLM and EBM processes. However, according to these studies, both SLM and EBM show unique metallurgical properties that have significantly effect on microstructure and mechanical properties of as-fabricated Ti alloys.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous investigations, scientists have confirmed the capability of heat treatment in decomposing nonequilibrium phase, [17][18][19][20] releasing residual stress, [12,21] and achieving columnar-to-equiaxed transition of β grains. [14,21] Therefore, heat treatment strategies successfully reduce the anisotropy and improve the strength-ductility trade-off of as-built Ti alloys. Furthermore, hot isostatic pressing (HIP) treatment is usually applied to eliminate the defects, thus the tensile property and fracture toughness of as-built samples can be improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] According to previous studies, [9][10][11][12][13][14] the microstructure of SLM-fabricated Ti alloys is nonequilibrium, owing to the aforementioned high cooling rates. For instance, α' martensite formed in some SLM-fabricated near α and α þ β Ti alloys, [11,14,15] because the solidification rate of SLM is much higher than the critical cooling rate required for martensite formation. The metastable α' martensite structure causes a high strength but a low ductility of as-SLMed Ti-alloy.…”
Section: Introductionmentioning
confidence: 99%